The Influence of Socio-Economic Factors on Farmers' Decision to Use Fertilization Technology in Paddy Rice Cultivation in Langgomea Village, Uepai District, Konawe Regency - Efriani, Efriani; La Ode Alwi; Ilma Sarimustaqiyma Rianse (International journal of technology and education research, 2024)
This study aims to: (1) to determine the influence of socio-economic factors (age, education level, number of family dependents, farming experience, land area and labor) on farmers' decisions to use Mist Blower fertilization technology and without Mist Blower in Langgomea Village, Uepai District, Konawe. The number of samples in this study were 60 people, Determination of samples in this study using the census method, The number of farmers who used Mist Blower was 28 farmers while those who did not use Mist Blower were 32 farmers. The method used is descriptive statistics and logistic regression analysis. The results of this study are socio-economic factors that influence the decisions of wet-rice farmers in using Mist Blower fertilization technology, namely the variable level of education and land area, while the variable age, number of family dependents, farming experience and labor do not affect farmers' decisions in using Mist Blower fertilization technology